Primary urinary bladder haemangiosarcoma in a captive saddleback tamarin (Saguinus fuscicollis) - Gonzales-Viera, Omar; Quevedo, Tatiana; Chavera, Alfonso; Perales-Camacho, Rosa; Grandi, Fabrizio [UNESP]; Catao-Dias, Jose L. (Wiley-Blackwell, 2014)
Background A captive adult male saddleback tamarin, Saguinus fuscicollis, was lethargic, unresponsive to its surrounding and died before medical care.Methods Necroscopic, histopathological and immunohistochemical examinations were performed.Results Neoplastic spindle cells of the urinary bladder were positive for anti-factor VIII antibody.Conclusion A primary urinary bladder haemangiosarcoma was diagnosed, and it has not been previously reported in non-human primates.
Keywords: neoplasm; non-human primate; tamarin; urinary system